2013
DOI: 10.1159/000350955
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Combined Antihypertensive Treatment (Felodipine with Either Irbesartan or Metoprolol) on Erectile Function: A Randomized Controlled Trial

Abstract: Objectives: This study aimed to determine whether combining a calcium channel blocker with either an angiotensin II receptor blocker or a β-blocker would have similar effects on sexual function in men with hypertension. Methods: This prospective, randomized study (ClinicalTrials.gov: NCT01​238705) included 218 male participants with untreated hypertension. Patients were randomized to treatment with felodipine combined with irbesartan or metoprolol for 48 weeks. Sexual function was evaluated at baseline and aft… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
12
0
2

Year Published

2013
2013
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(14 citation statements)
references
References 31 publications
(38 reference statements)
0
12
0
2
Order By: Relevance
“…Prospective randomized study in 218 males, over 48 weeks Randomized to treatment with felodipine combined with metoprolol or irbesartan No significant difference in prevalence of ED before or after treatment in either group Felodipine-irbesartan was more beneficial to the sexual desire of hypertensive males [145] Sexual activity and function in middle-aged and older men and women with HT National Opinion Research Center sample of 4017 l community-dwelling adults, 57-85 years, of whom 75.5 % completed the interview No consistent associations between specific antihypertensive medication classes and sexual problems, suggesting the need for prospective studies [149] Risk of falls after initiation of antihypertensive drugs in the elderly Population-based self-controlled study of elderly aged 66 Several factors contribute to nonadherence to medications and resultant suboptimal control of hypertension; poor tolerability due to ADEs is only one contributory factor. Anxiety sensitivity is strongly associated with antihypertensive drug nonadherence, a situation that can be managed through the use of adaptive strategies for anxiety, with resultant better control of hypertension and lower cardiovascular risk [166].…”
Section: Referencesmentioning
confidence: 93%
See 1 more Smart Citation
“…Prospective randomized study in 218 males, over 48 weeks Randomized to treatment with felodipine combined with metoprolol or irbesartan No significant difference in prevalence of ED before or after treatment in either group Felodipine-irbesartan was more beneficial to the sexual desire of hypertensive males [145] Sexual activity and function in middle-aged and older men and women with HT National Opinion Research Center sample of 4017 l community-dwelling adults, 57-85 years, of whom 75.5 % completed the interview No consistent associations between specific antihypertensive medication classes and sexual problems, suggesting the need for prospective studies [149] Risk of falls after initiation of antihypertensive drugs in the elderly Population-based self-controlled study of elderly aged 66 Several factors contribute to nonadherence to medications and resultant suboptimal control of hypertension; poor tolerability due to ADEs is only one contributory factor. Anxiety sensitivity is strongly associated with antihypertensive drug nonadherence, a situation that can be managed through the use of adaptive strategies for anxiety, with resultant better control of hypertension and lower cardiovascular risk [166].…”
Section: Referencesmentioning
confidence: 93%
“…An extensive review of several studies discussed the clinical impact of antihypertensives on sexual dysfunction: a table attributes largely neutral to negative impact for b-blockers (except nebivolol), diuretics, and ablockers; largely neutral or beneficial effects for ACEIs and ARBs; and neutral effects for CCBs [140]. The combination of a CCB (felodipine) with irbesartan appeared more beneficial to sexual desire in hypertensive males than the combination with metoprolol, perhaps attributed to the prevention of oxidative stress with irbesartan [145]. A Swedish study of 225 reports on antihypertensive drugs and ED suggested that all classes of drugs were implicated in ED, including ARBs, suggesting that ARBs had neither a positive nor any effect on ED [146].…”
Section: Sexual Dysfunctionmentioning
confidence: 99%
“…However, certain types of antihypertensive agents are likely to affect the efficacy of PDE5-Is in ED patients and even antihypertensive drug itself can impact some aspects of sexual function [6][7][8]. Angiotensin-converting enzyme inhibitors, angiotensin II receptor blockers, calcium channel blockers and alphablockers are less likely to cause ED while thiazide diuretics and some less selective beta-blockers (atenolol and carvedilol) may be detrimental to ED [9].…”
mentioning
confidence: 99%
“…In this issue of Cardiology, Yang et al [8] evaluated the effects of antihypertensive therapy on erectile function, comparing two combinations in a prospective randomized study. They recruited 218 male hypertensive patients, naive to antihypertensive therapy, and examined the combination of felodipine with either irbesartan or metoprolol for a follow-up period of 48 weeks.…”
mentioning
confidence: 99%
“…Moreover, the results of antihypertensive therapy remained consistent over time in the ONTARGET substudy [16], which was specifically designed to address this issue and is thus more reliable. Yang et al [8] followed their patients for 1 year, a period longer than the usual single-center studies but shorter than the typical multicenter trials in the hypertension field.…”
mentioning
confidence: 99%